Factors associated with severe maternal outcome in patients admitted to an intensive care unit in northeastern Brazil with postpartum hemorrhage: a retrospective cohort study - André Vieira Lanza; Melania Maria Amorim; Mayara Ferreira; Claúdia Menezes Cavalcante; Leila Katz (BMC, 2023)
Abstract Background Postpartum hemorrhage (PPH) is the leading cause of maternal death worldwide, particularly in low- and middle-income countries; however, the majority of these deaths could be avoided with adequate obstetric care. Analyzing severe maternal outcomes (SMO) has been a major approach for evaluating the quality of the obstetric care provided, since the morbid events that lead to maternal death generally occur in sequence. The objective of this study was to analyze the clinical profile, management, maternal outcomes and factors associated with SMO in women who developed PPH and were admitted to an obstetric intensive care unit (ICU) in northeastern Brazil. Methods This retrospective cohort study included a non-probabilistic, consecutive sample of postpartum women with a diagnosis of PPH who were admitted to the obstetric ICU of the Instituto de Medicina Integral Prof. Fernando Figueira (IMIP) between January 2012 and March 2020. Sociodemographic, biological and obstetric characteristics and data regarding childbirth, the management of PPH and outcomes were collected and analyzed. The frequency of maternal near miss (MNM) and death was calculated. Multiple logistic regression analysis was performed to determine the adjusted odd ratios (AOR) and their 95% confidence intervals (95% CI) for a SMO. Results Overall, 136 cases of SMO were identified (37.9%), with 125 cases of MNM (34.9%) and 11 cases of maternal death (3.0%). The factors that remained associated with an SMO following multivariate analysis were gestational age ≤ 34 weeks (AOR = 2.01; 95% CI: 1.12-3.64; p < 0.02), multiparity (AOR = 2.20; 95% CI: 1.10-4.68; p = 0.02) and not having delivered in the institute (AOR = 2.22; 955 CI: 1.02-4.81; p = 0.04). Conclusion Women admitted to the obstetric ICU with a diagnosis of PPH who had had two or more previous deliveries, gestational age ≤ 34 weeks and who had delivered elsewhere were more likely to have a SMO.